2023
DOI: 10.3390/cells12040666
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Signaling Influences Nephron Segmentation of the Zebrafish Embryonic Kidney

Abstract: Despite significant advances in understanding nephron segment patterning, many questions remain about the underlying genes and signaling pathways that orchestrate renal progenitor cell fate choices and regulate differentiation. In an effort to identify elusive regulators of nephron segmentation, our lab conducted a high-throughput drug screen using a bioactive chemical library and developing zebrafish, which are a conserved vertebrate model and particularly conducive to large-scale screening approaches. 17β-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…In our study, we found that exogenous treatment of E2 resulted in specific changes to the distal pronephros, where the DE was increased at the expense of the neighboring DL segment (Wesselman et al, 2023). A selective estrogen receptor modulators (SERM) screen revealed that this phenotype was largely due to Esr2 activity, as inhibition with PHTPP resulted in the opposite phenotype (Wesselman et al, 2023b).…”
Section: Kidneymentioning
confidence: 76%
See 1 more Smart Citation
“…In our study, we found that exogenous treatment of E2 resulted in specific changes to the distal pronephros, where the DE was increased at the expense of the neighboring DL segment (Wesselman et al, 2023). A selective estrogen receptor modulators (SERM) screen revealed that this phenotype was largely due to Esr2 activity, as inhibition with PHTPP resulted in the opposite phenotype (Wesselman et al, 2023b).…”
Section: Kidneymentioning
confidence: 76%
“…Using the zebrafish as a model to investigate developmental pathways of kidney formation, chemical screens have identified several chemical regulators of interest, including estrogen signaling (Poureetezadi et al, 2016;Wesselman et al, 2023). Identifying a link between estrogen signaling and nephron development was surprising, as estrogen has traditionally been considered a sex hormone, with most research focusing on gonad development.…”
Section: Kidneymentioning
confidence: 99%
“…Further research is required to interrogate the mechanism by which the distal tubule segment is regulated. Candidate transcription factors like tbx2b may be of interest, as it operates downstream of ppargc1a in establishing distal cell fate identity ( Chambers et al, 2018 ; Drummond et al, 2017 ), as well as mecom , tbx2a , emx1 , gldc and esr2b , which are also essential for distal segment fate ( Drummond et al, 2017 ; Li et al, 2014 ; Morales et al, 2018 ; Weaver et al, 2022 ; Wesselman et al, 2023c ). Although continued kidney research in animal models such as zebrafish affords the opportunity to dissect gene functions and model renal diseases like ciliopathies, parallel studies in mammalian models are also essential ( Corkins et al, 2021 ; McKee and Wingert, 2015 ; Molinari and Sayer, 2020 ; Morales and Wingert, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have discussed several critical advances in delineating the genetic factors which dictate lineage fate choice and differentiation of nephron segments in the zebrafish embryonic kidney. Ongoing work continues to identify genes of interest [ 154 , 155 , 156 , 157 ]. Continued investigations to elucidate the interrelationships and functions of these identified factors are an exciting future area of investigation.…”
Section: Discussionmentioning
confidence: 99%